Dominant aminoacyl-tRNA synthetase disorders: lessons learned from in vivo disease models - Kalotay, Elizabeth; Klugmann, Matthias; Housley, Gary D.; Fröhlich, Dominik (Frontiers in Neuroscience, 2023)
Aminoacyl-tRNA synthetases (ARSs) play an essential role in protein synthesis, being responsible for ligating tRNA molecules to their corresponding amino acids in a reaction known as ‘tRNA aminoacylation’. Separate ARSs carry out the aminoacylation reaction in the cytosol and in mitochondria, and mutations in almost all ARS genes cause pathophysiology most evident in the nervous system. Dominant mutations in multiple cytosolic ARSs have been linked to forms of peripheral neuropathy including Charcot-Marie-Tooth disease, distal hereditary motor neuropathy, and spinal muscular atrophy. This review provides an overview of approaches that have been employed to model each of these diseases in vivo, followed by a discussion of the existing animal models of dominant ARS disorders and key mechanistic insights that they have provided. In summary, ARS disease models have demonstrated that loss of canonical ARS function alone cannot fully account for the observed disease phenotypes, and that pathogenic ARS variants cause developmental defects within the peripheral nervous system, despite a typically later onset of disease in humans. In addition, aberrant interactions between mutant ARSs and other proteins have been shown to contribute to the disease phenotypes. These findings provide a strong foundation for future research into this group of diseases, providing methodological guidance for studies on ARS disorders that currently lack in vivo models, as well as identifying candidate therapeutic targets.